2014
DOI: 10.1007/s11661-014-2631-4
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synchrotron Radiation Study of TiH2-6Al-4V and Ti-6Al-4V: Accelerated Alloying and Phase Transformation, and Formation of an Oxygen-Enriched Ti4Fe2O Phase in TiH2-6Al-4V

Abstract: In situ heating, synchrotron radiation X-ray diffraction has been used to study the alloying and phase transformation behavior of TiH 2 -6Al-4V and Ti-6Al-4V alloys. Accelerated alloying and phase transformation were observed in the powder compact of the TiH 2 -6Al-4V alloy subjected to a high heating rate. In addition, an oxygen-stabilized Ti 4 Fe 2 O phase, which is present as sub-micron or nanoscaled particles, has been identified in the TiH 2 -6Al-4V alloy. The implications of these experimental findings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The figure shows that the as-built density of AM Ti-6Al-4V is mostly higher than 99% of theoretical density and the material can be fully dense if processing parameters are appropriately selected. SLS Ti-6Al-4V is exceptional to this conclusion, which as-built densities are around 95% and similar to the as-sintered density of the conventional PM Ti-6Al-4V [4][5][6][7][8][9][10][11][12][13]. …”
Section: Densification Of Am Ti-6al-4vmentioning
confidence: 72%
See 2 more Smart Citations
“…The figure shows that the as-built density of AM Ti-6Al-4V is mostly higher than 99% of theoretical density and the material can be fully dense if processing parameters are appropriately selected. SLS Ti-6Al-4V is exceptional to this conclusion, which as-built densities are around 95% and similar to the as-sintered density of the conventional PM Ti-6Al-4V [4][5][6][7][8][9][10][11][12][13]. …”
Section: Densification Of Am Ti-6al-4vmentioning
confidence: 72%
“…The high cost of the ELI raw powders, however, can be an issue to AM Ti-6Al-4V from cost perspective. Figure 22 compares the price of a variety of powders, showing that the cost on the AM powders is extraordinary [4][5][6][7][8][9][10][11][12][13]. They are mostly higher than $400 per kg while hydrogenation-dehydrogenation (HDH) Ti powders that are widely used in conventional PM Ti are merely around $30 per kg.…”
Section: Dependence Of α Colony Size On Heat Treatment and Microstrucmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that, under certain circumstances, less expensive alloying elements may have beneficial effects on PM Ti alloys [354]. For example, Yan et al [355] postulated that the reaction kinetics between Ti and Fe are accelerated when TiH 2 powder is used as the feedstock in a PM process. Therefore, it was proposed that this phenomenon could enable the use of Fe to scavenge oxygen in PM Ti alloys via the formation of submicron Ti 4 Fe 2 O particles.…”
Section: Static Propertiesmentioning
confidence: 99%